Detection of HIFU lesions in Excised Tissue Using Acousto-Optic Imaging - Draudt, A; Lai, P; Roy, R; Murray, T; Cleveland, R (2009)
Real-time imaging of the heating of tissue and lesion formation is a major barrier to the clinical application of HIFU. Tissue necrosis results in a change in the optical properties of the tissue. We have employed the acousto-optical (A-O) interaction to image HIFU lesions formed in excised chicken breast. The tissue was illuminated with infrared light (1064 nm wavelength) resulting in a diffuse optical field throughout the tissue. Simultaneously, the tissue was insonified with a diagnostic ultrasound imager running in B-mode. The photons that passed through the region of tissue where the pulsed 5 MHz ultrasound beam was present were phase modulated by the sound field. These modulated photons were detected by means of an interferometric detector employing a photorefractive crystal (PRC). To first order the amplitude of the output from the PRC is related to the optical absorption of the tissue where the sound was present. By firing multiple acoustic beams along different pathways, the spatially dependent optical absorption coefficient (uncalibrated) within a tissue region of interest is determined and presented in the form of a 2-D image. Images thus generated were recorded in chicken breast before and after HIFU exposure (1.1 MHz, 6 s duration, 6 MPa peak pressure). The acoustic and optical beams were scanned across the tissue, and the waveforms combined to form a 2-D AO image. The imaged lesion size of 9 x 2 mm 2 agreed well with the measured lesions size 10 x 3 mm 2. © 2009 American Institute of Physics.